Establishing a causal link between social relationships and health using the Bradford Hill Guidelines - Howick, J; Kelly, P; Kelly, M (Elsevier, 2019)
An abundance of evidence suggests that the size and quality of our social relationships improves humans' physical and mental health while increasing lifespan. However most of this evidence comes from observational rather than experimental (randomised trial) evidence, leaving open the possibility that the connection between social relationships and health could be associational rather than causal. However there are examples, including the link between smoking and lung cancer, where a cause was established without experimental evidence. This was sometimes achieved by looking at the totality of evidence, using the ‘Bradford Hill Guidelines’, which considers factors including the strength of association, reversibility, and evidence of a plausible mechanism. In this paper we apply the Bradford Hill Guidelines to the link between social relationships and health. We conclude that having strong and supportive social relationships causes better health and longer life. Beyond establishing that social relationships are a causal factor for health, the method we used here can be applied to other areas where randomised trials are unethical or not feasible.